2011
DOI: 10.1016/j.jmb.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain Conformational Changes upon Protein–Protein Association

Abstract: Conformational changes upon protein-protein association are the key element of the binding mechanism. The study presents a systematic large-scale analysis of such conformational changes in the side chains. The results indicate that short and long side chains have different propensities for the conformational changes. Long side chains with three or more dihedral angles are often subject to large conformational transition. Shorter residues with one or two dihedral angles typically undergo local conformational ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 72 publications
4
42
0
Order By: Relevance
“…While several studies have shown the importance of side-chain conformations in flexible protein-protein associations (Beglov et al, 2012; Ehrlich et al, 2005; Rajamani et al, 2004; Ruvinsky et al, 2011), manipulation of backbone flexibility on docking is less well explored. Torsion angle dynamics simulations of the barnase–barstar complex (Ehrlich et al, 2005) showed that barnase could not reach barstar from the unbound starting structures unless the bound-state loop conformation and hot spot residue pair were grafted onto the unbound structures.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have shown the importance of side-chain conformations in flexible protein-protein associations (Beglov et al, 2012; Ehrlich et al, 2005; Rajamani et al, 2004; Ruvinsky et al, 2011), manipulation of backbone flexibility on docking is less well explored. Torsion angle dynamics simulations of the barnase–barstar complex (Ehrlich et al, 2005) showed that barnase could not reach barstar from the unbound starting structures unless the bound-state loop conformation and hot spot residue pair were grafted onto the unbound structures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that one-third of all interface residues are observed to undergo conformational changes (87,88). These changes result in an entropic cost by being restricted to one rotamer conformation and an enthalpic cost by breaking the noncovalent intramolecular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Moreover, in recent analyses, it has been shown that interface residues were more frequently found in high-energy torsion angle state 29 and side-chain conformation changes due to protein-protein association. 30 Therefore, we asked how side-chain conformational changes are associated with multiple binding. To address this point, we identified sets of equivalent residues in the OV and Non-OV regions from multiple sequence alignments (MSAs) and analyzed diversity of sidechain χ1 angles in each such set of residues ( Fig.…”
Section: Residue Compositions In the Ov And Non-ov Regionsmentioning
confidence: 99%